2021
DOI: 10.1371/journal.pgen.1009445
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of C9orf72 haplotypes to evaluate the effects of normal and pathological variations on its expression and splicing

Abstract: Expansion of the hexanucleotide repeat (HR) in the first intron of the C9orf72 gene is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) in Caucasians. All C9orf72-ALS/FTD patients share a common risk (R) haplotype. To study C9orf72 expression and splicing from the mutant R allele compared to the complementary normal allele in ALS/FTD patients, we initially created a detailed molecular map of the single nucleotide polymorphism (SNP) signature and the HR leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…However, our results showed that a substantial fraction of C9 NRE-containing transcripts used the Ex1b splice donor, which may be in part due to its proximity to the NRE compared to the other downstream splice donors. Notably, some downstream cryptic 5ʹ splice sites, including those of exon 1c and 1d, have previously been observed in C9 NRE + iPSCs 43 , although it was not known whether C9 NRE was part of these transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results showed that a substantial fraction of C9 NRE-containing transcripts used the Ex1b splice donor, which may be in part due to its proximity to the NRE compared to the other downstream splice donors. Notably, some downstream cryptic 5ʹ splice sites, including those of exon 1c and 1d, have previously been observed in C9 NRE + iPSCs 43 , although it was not known whether C9 NRE was part of these transcripts.…”
Section: Discussionmentioning
confidence: 99%